THE POLEMIC ON THE RENOVATION OF THE JAKARTA INTERNATIONAL STADIUM (SOCIAL AND POLITICAL PERSPECTIVE) - Karateng, Mastura; Kalalo, Rieneke Ryke; Sari, Ade Risna; Wibisono, Okki Navarone; Munizu, Musran (ITB AAS Indonesia Surakarta, 2024)
Abstract The Jakarta International Stadium, abbreviated as JIS, was claimed by the Minister of PUPUR, the Minister of SOEs who is also the General Chair of PSSI, and the leadership of PT. Rama Prima's work does not meet FIFA standards and must be renovated immediately. This has caused a polemic among the people because JIS has been a symbol of achievement echoed by former governor of DKI Jakarta Anis Rasyid Baswedan. Therefore, this study aims to comprehensively analyze the polemic of JIS renovation from a social and political perspective. From the social side, this researcher uses the theory of Symbolic Interactionism. Meanwhile, from a political perspective, this research relates Anis Rasyid Baswedan as a presidential candidate and Erick Thohir as a vice presidential candidate. This research is a qualitative research with a descriptive approach. Data collection techniques through the library method and analyzed using observation, selection, reduction and conclusion analysis techniques. The results of the research show that the fairness of JIS claims that are not FIFA standards has sparked polemics in the community and it is better if these claims are immediately announced by FIFA. In addition, this polemic is very easily associated with politics because Anis Rasyida Baswedan is a presidential candidate and Erickt Thohir is a vice presidential candidate who has the highest electability compared to other candidates. Keywords : Polemic, Jakarta International Stadium, Social, Political.